Pusa Prabhat (HI 8823) a high yielding, drought tolerant and biofortified durum wheat variety for central wheat growing zone of India - Ambati, Divya; M Phuke, Rahul; SV, Sai Prasad; Singh, JB; TL, Prakasha; Sharma, KC; Singh, AK; verma, DK; Mishra, AN; Singh, GP; Sharma, JB; Singh, PK; et al. (Journal of Cereal Research, 2023)
Pusa Prabhat (HI 8823), a high yielding durum wheat variety which was released and notified by Central Sub-Committee on Crop Standards, Notification and Release of Varieties for Agricultural Crops, Government of India for commercial cultivation for timely sown, restricted irrigation conditions of central Zone vide notification number S.O. 8 (E) dated 03.01.2022. HI 8823 recorded an average yield of 38.5q/ha and a potential yield of 65.6 q/ha. HI 8823 offers to be a best variety for central zone wheat farmers with good amount of protein (12.1%), yellow pigment (7.2ppm), micro nutrient content(>37ppm), over all pasta acceptability(6) and recorded to be resistant to major pests and diseases. Hence, it can provide excellent raw material for the upcoming semolina-based industries and essential nutrients needed for sound health of the country as a biofortifed durum wheat variety.